A micromechanical model of carbon fiber-reinforced plastic and steel hybrid laminate composites. (September 2021) - Sung, Minchang; Ahn, Hyunchul; Jang, Jinhyeok; Kwon, Dongil; Yu, Woong-Ryeol
The fracture strain of carbon fiber-reinforced plastics (CFRPs) within CFRP/steel hybrid laminate composites is reportedly higher than that of CFRPs due to transverse compressive stress induced by the steel lamina. A micromechanical model was developed to explain this phenomenon and also to predict the mechanical behavior of CFRP/steel hybrid laminate composites. First, the shear lag theory was extended to calculate stress distributions on fibers and matrix material in a CFRP under multiaxial stress condition, considering three deformation states of matrix (elastic and plastic deformation and fracture) and the transverse compressive stress. Then, the deformation behavior of CFRP was predicted using average stress in the ineffective region and the Weibull distribution of carbon fibers. Finally, the mechanical properties of CFRP/steel hybrid laminate composites were predicted by considering the thermal residual stress generated during the manufacturing process. The micromechanical model revealed that increased transverse compressive stress decreases the ineffective lengths of partially broken fibers in the CFRP and results in increased fracture strain of the CFRP, demonstrating the validity of the current micromechanical model.